Adaptive demand response to improve economic performance of microgrids - Gao, Yue (2015)
Recently, increased attention has been focused on the demand response (DR), especially in the smart grid environment, where bi-directional communication can be implemented between smart meters and power grid. The smart household appliances can be controlled to actively respond to the control and frequency regulation requirement of the power grid. The coordinated control can be carried out by using quick response resources, spinning reserves, and a comprehensive DR scheme for frequency regulation. Demand response is adopted as the first load shedding option to avoid the unexpected load shedding, thus the economic performance can be improved. Through the coordination of smart demand response with spinning reserves, the substantial drop of system frequency can be prevented, and the frequency could be restored back to around the rated value quickly, thus the flexibility and reliability of power grid can be improved. Finally, the consumers’ comfort is considered to evaluate the demand response involved in the frequency regulation. Simulations have been carried out on a low order system frequency response (SFR) model. The simulation results show that the proposed scheme could restrict the fault-caused frequency drop quickly, enhance the security of the power system and effectively reduce the expense for load shedding.